2019
DOI: 10.21603/2308-4057-2019-1-60-66
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein-containing additives on pasta quality and biological value

Abstract: The present work includes results on enrichment of pasta, a mass-consumption product, with protein. Meat products, legume (Leguminosae L.) flour and plant protein isolates were used as protein-containing additives. The content of protein and essential amino acids in the additives makes them promising for improving the biological value of pasta. We studied effects of the additives on raw gluten and wheat flour starch properties, pasta dough rheo- logical characteristics, and finished product quality. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Thus, the addition of WGPI resulted in a high protein product with complete protein. Obtaining a complete protein according to the FAO standard was also attempted by adding pea protein isolate at 10% (Osipova et al, 2019), but threonine was found to be the limiting amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the addition of WGPI resulted in a high protein product with complete protein. Obtaining a complete protein according to the FAO standard was also attempted by adding pea protein isolate at 10% (Osipova et al, 2019), but threonine was found to be the limiting amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…In pasta the types pasta composition industry, only an were increase confirms in obtained the from nutritional shape and economy biological grinding value free of tryptophan products legumes is degrees achieved trypsin through necessary the chickpea introduction effect of prepared non-dispersed traditional laboratory raw shown materials prepared and wheat special flour food application additives fine into also the products formulation. Albumin the called greatest known positive minerals effect flour in dispersed increasing improving the highest nutritional quality and acid biological processing value pasta of legume pasta starch products other can pasta be kulazhanov achieved protein by economy the chickpea use amino of evaluated legume body crops chickpea processing content products [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%